2005
DOI: 10.1007/s00122-004-1890-7
|View full text |Cite
|
Sign up to set email alerts
|

Gene actions of QTLs affecting several agronomic traits resolved in a recombinant inbred rice population and two backcross populations

Abstract: To understand the types of gene action controlling seven quantitative traits in rice, we carried out quantitative trait locus (QTL) mapping in order to distinguish between the main-effect QTLs (M-QTLs) and digenic epistatic QTLs (E-QTLs) responsible for the trait performance of 254 recombinant inbred lines (RILs) from rice varieties Lemont/Teqing and two backcross hybrid (BCF1) populations derived from these RILs. We identified 44 M-QTL and 95 E-QTL pairs in the RI and BCF1 populations as having significant ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

34
133
2
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(175 citation statements)
references
References 15 publications
34
133
2
6
Order By: Relevance
“…The additive QTL do not contribute to heterosis, while the non-additive QTL, including dominant, overdominant, and epistatic do contribute [12,15,19,22,24,25,28]. The second one is to use the measurements of heterosis as the data input to perform QTL analysis [13][14][15][24][25][26]30,43]. QTL effects for Z 1 and Z 2 in the RIL-based NCIII design provide estimates of the augmented effects a*, which measures the net contribution of the QTL to the parental difference, and d*, which measures the net contribution of the QTL to midparent heterosis [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The additive QTL do not contribute to heterosis, while the non-additive QTL, including dominant, overdominant, and epistatic do contribute [12,15,19,22,24,25,28]. The second one is to use the measurements of heterosis as the data input to perform QTL analysis [13][14][15][24][25][26]30,43]. QTL effects for Z 1 and Z 2 in the RIL-based NCIII design provide estimates of the augmented effects a*, which measures the net contribution of the QTL to the parental difference, and d*, which measures the net contribution of the QTL to midparent heterosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Another modification of the NCIII design is to use recombinant inbred lines (RIL) as the base population. The results showed that the primary genetic basis of heterosis is dominance in the interval mapping by Xiao et al [22], and epistasis and overdominance in the mixed model analysis [23] by Li et al [24], Luo et al [25] and Mei et al [26]. It should be noted that repulsion linkage might lead to pseudo-overdominance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RM235 was associated with spikelet fertility QTL qHt12 on chromosome 12 with 10 % phenotypic variance in heat stress treatment during flowering stage . This marker was also linked to leaf width in RIL population of cross Lemont × Teqing and two backcross hybrid populations derived from these RILs (Mei et al 2005). Jagadish et al (2010a) reported qtl_2.3 for spikelet fertility in control conditions and the allele was contributed by Azucena, a susceptible parent.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, genetic models for QTL mapping assuming no epistasis can lead to a biased estimation of QTL parameters (Bocianowski 2013). A large number of epistatic effects have recently been detected in rice (Oryza sativa L.) using polymorphic markers in the whole genome (Hua et al 2002;Mei et al 2003Mei et al , 2005. Epistatic effects have been found to be important in the expression of dough rheological properties in a wheat DH population (Ma et al 2005).…”
Section: Discussionmentioning
confidence: 99%